Kebijakan Penyuluhan Keluarga dalam Pembentukan Karakter Anak Melalui Pendekatan Dakwah di Kabupaten Mamuju, Sulawesi Barat - Rustan (JURNAL ILMIAH GEMA PERENCANA, 2024)
This policy paper describes the family counseling policy to shape children's character through a da'wah approach by Religious Counselors in Mamuju Regency, West Sulawesi. This article aims to present a family counseling program that has a strategic role in forming children's character by assisting Islamic Religious Counselors to parents using a da'wah approach. This study uses qualitative methods in managing data obtained through interviews and direct observation, both from primary and secondary sources, then conducting in-depth interviews and field observations which are analyzed in detail regarding the role of Islamic Religious Counselors in carrying out child counseling. This policy paper reveals that family counseling policies aim to shape children's character by adopting a da'wah approach that includes forms of da'wah, such as bil-hikmah, bil-mau'idzah, and bil-mujjadi, as taught in the QS. an-Nahl [16]: 125. These findings imply that family counselors need to take the role of positive models who are full of empathy and promote honesty and patience in their words and actions. In addition, persuasive guidance is considered an effective approach to forming children's character through da'wah.